Types of Translation, Criteria for Dividing Translation into Types (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
In translation studies, different types of translation can be distinguished depending on the form of the material in the original language and the translated language. This is the basis for the first classification. In translation studies, the types of translation are distinguished based on their content and essence, in which translation is classified based on their content or essence rather than the form of the texts in both languages.